8‐2: Invited Paper: A New Generation of Luminescent Materials Based on Low‐Dimensional Perovskites. Issue 1 (2nd June 2017) - Pan, Jun; Sinatra, Lutfan; Lutfullin, Marat; Dursun, Ibrahim; Bakr, Osman M.
Abstract : Low‐dimensional perovskites with high luminescence properties are promising materials for optoelectronic applications. In this article, properties of two emerging types of low‐dimensional perovskites are discussed, including perovskite quantum dots CsPbX3 (X = Cl, Br or I) and zero‐dimensional perovskite Cs4 PbBr6 . Moreover, their application for light down conversion in LCD backlighting systems and in visible light communication are also presented. With their superior optical properties, we believe that further development of these materials will potentially open more prospective applications, especially for optoelectronics devices.